Synthesis and Properties of Fumaric Copolymers as Potential Bitumen Modifiers. Issue 4 (4th March 2019) - Oberti, Tamara G.; Larsen, Diego; Cortizo, M. Susana
ABSTRACT: New copolymers of dioctyl fumarate (DOF) and styrene (S) were synthetized by radical polymerization and used to modify bitumen. The poly(dioctyl fumarate-co-styrene) copolymers, PFS, were characterized by 1 H-NMR and FTIR spectroscopies and size exclusion chromatography (SEC) in order to determine their monomer composition and weight average molecular weights, respectively. The polymer-bitumen blending conditions were optimized and the samples analyzed by different methodologies. Fluorescence microscopy, rotational viscosity and differential scanning calorimetry (DSC) were used to study the morphological changes of blends during their manufacturing and the rheological and thermal behavior, respectively. All modified bitumen (MB) exhibited higher viscosity than the based bitumen (BB) under studied conditions and this effect was more evident for the MB containing the higher molecular weight polymer. The addition of polymers to BB enhances the bitumen viscosity and thus increased the energy required for the flowing (activation energy calculated by Arrhenius equation). Thermal and morphological analysis showed that all MB exhibited good polymer- bitumen compatibility, which could be consider as a good starting point for a potential applications of this new material in road engineering. GRAPHICAL ABSTRACT: GRAPHICAL ABSTRACT